A regulamentação do uso e ocupação do solo urbano para fins residenciais na cidade de Ponta Grossa/PR no período de 1988 a 2018 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
The following research aims to study urban policy, narrowed down to the analysis of the urbanistic instruments for zoning, use, and occupation of urban land for residential purposes in the city of Ponta Grossa-PR, contextualized in the period immediately following the 1988 Constitution of the Federative Republic of Brazil (CF/88), up until 2018, which represents the milestone of three decades of constitutionalizing urban policy. The hypothesis is that the local law regarding spatial planning, upon being altered to allow and/or encourage private investments, works as an instrument to ease the use and occupation of urban land, therefore allowing and stimulating a differentiated appropriation of the city for different social classes. The research was built upon the critical theory perspective of urban studies, which understands space as a material dimension of the social reality, where social relations of production are made and reproduced; and, as the city is a privileged spot from which to observe social phenomena, it is where the contradictions between private and collective interests become most apparent. The research is exploratory, as well as quantitative and qualitative in its nature, and built from the perspective of the dialectic method, taking into consideration the categories of historicity, totality, and contradiction. The methodological instrument adopted was the bibliographical and documental research. The empirical research field is comprised of the city of Ponta Grossa-PR, with the purpose of understanding the changes that the local law regarding spatial planning (Lei nº 6.329/1999) caused to the production of local residential urban space. First, there was an analysis of the changes made to the law, concerning the modification of zoning, arriving at the grand total of 132 legal amendments between 1999 and 2018. Next, there was the process of spatially identifying and classifying which districts in the city had the highest number of legal interventions, which were: Centro, Uvaranas, Oficinas, Estrela, Jardim Carvalho, Órfãs, and Nova Rússia. Subsequently, gathering data from the real estate sector, it was possible to identify that the districts with the sharpest increase in value were the ones receiving the most legal interventions in their zoning – the reason why the research was restricted to those seven districts. Thus, in order to understand the changes that happened to the urban space following legal alterations, there was the process of facing the places altered by amendments with permits dispatched by the city’s Executive branch after the alterations, to establish the existence of a relation between the legal amendments and the changes in the way of using and occupying the land for residential purposes in the city, therefore verifying which interests were looked after when the alterations to urban zoning took place in Ponta Grossa-PR. The first chapter focused on the construction of conceptual theory reflections concerning the production of urban space, encompassing the agents and strategies related to this process, as well as taking back the main milestones of Brazilian urbanization and the insertion of the urban matter as a matter of the State, later dealing with urban policy in Brazil. The second chapter focused on the local reality of Ponta Grossa- PR, considering historical and geographical aspects of the way the city was formed, besides the socioeconomical profile of the last three decades, leading to the structure of the city’s urban legislation, in particular the law for zoning, use and occupation of urban land (Lei 6.329/1999) and its implications for the production of urban space. The third chapter intended to confront the data that was collected, to extract and debate the results of the changes that occurred to the residential urban space after the amendments to the law for zoning, use and occupation of land. Among the research results, the key highlights are, firstly, the absence of urban planning to make the legal alterations given the lack of technical studies. The identification of the city’s Legislative branch as one of the main agents in producing the urban space of Ponta Grossa. The connivance of the Executive branch towards the Legislative branch’s stance, in not promoting the guidelines of the city’s statute and development plan. Spatially, there was the realization that the amendments have changed the urban residential space of the city, increasing verticalization; after 2011, there was, especially, high-class verticalization, in the best areas of the city, destined to the upper classes, favoring the interests of real estate agents, proving the sustainability of the hypothesis that was initially brought up.
Keywords: Política pública; Política urbana; Uso e ocupação do solo; Zoneamento; Ponta Grossa- PR; Public policy; Urban policy; Use and occupation of land; Zoning; Ponta Grossa-PR; CNPQ::CIENCIAS SOCIAIS APLICADAS